Achieving geoeconomic goals by boosting the economy without raising the public debt ratio? New evidence on the effects of public investment in the European Union - Philipp Heimberger; Cara Dabrowski (The Vienna Institute for International Economic Studies (wiiw), 2025)
Public investment can support geoeconomic policy goals by strengthening economic resilience through the creation of public assets and by fostering domestic sources of economic growth. This paper presents new evidence on how public investment affects output, unemployment, private investment and public debt in the 27 EU member countries. Using forecast errors based on archival data to identify public investment shocks, we find that expansionary shocks (a) have favourable effects on output and unemployment in the short to medium run; (b) do not crowd out private investment; and (c) do not jeopardise public debt sustainability. Even though fiscal consolidation pressures linked to EU fiscal rules are high, promoting public investment may be critical - not only for economic development, but also to advance geostrategic goals in energy, infrastructure and resilience.
Keywords: E32; D84; F02; Q41; Q43; Q48; 330; Public investment; growth; unemployment; public debt